2019
DOI: 10.1037/edu0000306
|View full text |Cite
|
Sign up to set email alerts
|

Expanding autonomy psychological need states from two (satisfaction, frustration) to three (dissatisfaction): A classroom-based intervention study.

Abstract: We propose that students experience "autonomy dissatisfaction" when the learning environment is indifferent to their psychological need for autonomy. We hypothesized that (1) students could distinguish this newly-proposed need state from both autonomy satisfaction and autonomy frustration, (2) autonomy dissatisfaction would explain unique and rather substantial variance in students' classroom disengagement, and (3) a full understanding of the psychological need for autonomy necessitates expanding the current e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 89 publications
8
74
0
3
Order By: Relevance
“…In addition, the high correlations found in the present study between the behavioral and emotional indicators suggest uniqueness. For this two-factor model, different studies have been successfully conducted in different contexts, like academic [44,45] and PE class [46]. However, these results differ from other studies [12,20,28,47], which support the four-dimension model, since it presented the best fit indexes and moderate correlation values between the behavioral and emotional indicators, that is, in the results of these works, the factors are related but distinguishable from each other.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the high correlations found in the present study between the behavioral and emotional indicators suggest uniqueness. For this two-factor model, different studies have been successfully conducted in different contexts, like academic [44,45] and PE class [46]. However, these results differ from other studies [12,20,28,47], which support the four-dimension model, since it presented the best fit indexes and moderate correlation values between the behavioral and emotional indicators, that is, in the results of these works, the factors are related but distinguishable from each other.…”
Section: Discussionmentioning
confidence: 70%
“…However, in testing for evidence of differential predictive utility using structural equation modeling (SEM), the authors reported need dissatisfaction to have poor predictive effects, as it failed to predict the outcome measures of interpersonal competence (index of optimal functioning) and interpersonal sensitivity (index of diminished functioning) uniquely. Costa and colleagues' (2015) attempt to assess the predictive ability of need dissatisfaction was speculated to be unsuccessful due to the outcomes they employed (Cheon et al, 2019). For instance, in the past, need frustration has been demonstrated to best predict "darker" outcomes associated with maladaptive functioning (e.g., burnout and disordered eating, Bartholomew et al, 2011b).…”
Section: Basic Psychological Need Satisfaction Frustration and Unfumentioning
confidence: 99%
“…For instance, in the past, need frustration has been demonstrated to best predict "darker" outcomes associated with maladaptive functioning (e.g., burnout and disordered eating, Bartholomew et al, 2011b). Need dissatisfaction, on the other hand, has been proposed to be a better predictor of more passive forms of maladaptive functioning, such as disengagement and boredom (Cheon et al, 2019).…”
Section: Basic Psychological Need Satisfaction Frustration and Unfumentioning
confidence: 99%
“…Teachers' autonomy support refers to a group of behaviors that encourage student intrinsic motivation by offering students meaningfull choices, attempting to understand their perspectives, providing them with personally meaningful rationales for task engagement, encouraging their input in decision making processes, and giving them opportunities for self-initiated behavior (Cheon et al, 2019). Stefanou, Perencevich, DiCintio and Turner (2004) distinguish three ways teachers' autonomy support manifests in the classroom: organizational autonomy support, procedural autonomy support and cognitive autonomy support.…”
Section: Introductionmentioning
confidence: 99%